Prophylaxis for iron deficiency anemia using ferrous sulfate among infants followed up at a primary healthcare unit in the municipality of Embu-SP (2003/2004) - André Fernando Shibukawa; Edina Mariko Koga da Silva; Wilson André Ichiki; Maria Wany Louzada Strufaldi; Rosana Fiorini Puccini (São Paulo Medical Journal)
CONTEXT AND OBJECTIVE: Iron deficiency anemia is an important public health problem in Brazil. In the municipality of Embu, a population study in 1996 found anemia prevalence of 68.5% among children aged one to two years. From these data, prescription of prophylactic ferrous sulfate was instituted in 1998 for children under two years old followed up within the children's healthcare program. After five years of intervention, the prevalence of anemia and associated factors were investigated among children aged 12 to 18 months to whom guidance for prophylactic ferrous sulfate use had been given. DESIGN AND SETTING: Cross-sectional study covering October 2003 to June 2004 at a primary healthcare unit in Embu. METHODS: A randomized sample of children aged 12 to 18 months to whom guidance for prophylactic ferrous sulfate use had been given was obtained. Hemoglobin was measured in capillary blood, using HemoCue® apparatus. Hemoglobin < 11 g/100 dl was taken to indicate anemia. RESULTS: The sample comprised 118 children and anemia was found in 41.5%. There was no statistically significant association between anemia presence and the variables of sex, birth weight, neonatal intercurrences, chronic diseases, breastfeeding or iron supplementation use. There was a statistically significant association (p = 0.03) between anemia presence and per capita income, such that the higher the income was, the lower the prevalence of anemia was. CONCLUSION: The prophylaxis program against iron deficiency anemia did not achieve the expected results. New strategies must be considered in the light of the magnitude of the problem.